2013
DOI: 10.1021/jp402140t
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the Helical Wrapping of Phenyleneethynylene Polymers about Single-Walled Carbon Nanotubes

Abstract: The highly charged, conjugated polymer poly[p-{2,5-bis(3-propoxysulfonicacidsodiumsalt)}phenylene]ethynylene (PPES) has been shown to wrap single-wall carbon nanotubes (SWNTs), adopting a robust helical superstructure. Surprisingly, PPES adopts a helical rather than a linear conformation when adhered to SWNTs. The complexes formed by PPES and related polymers upon helical wrapping of a SWNT are investigated using atomistic molecular dynamics (MD) simulations in the presence and absence of aqueous solvent. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…In a previous molecular dynamics (MD) study, Saven and co-workers demonstrated that poly(phenylene ethynylene)s could adhere to the surface of SWNTs forming a robust helical superstructure. 10 Polymers 1 and 2 were thus envisioned to take a unique ''centipede-like'' wrapping mode to result in highly efficient SWNT dispersion in organic solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous molecular dynamics (MD) study, Saven and co-workers demonstrated that poly(phenylene ethynylene)s could adhere to the surface of SWNTs forming a robust helical superstructure. 10 Polymers 1 and 2 were thus envisioned to take a unique ''centipede-like'' wrapping mode to result in highly efficient SWNT dispersion in organic solvents.…”
mentioning
confidence: 99%
“…For HiPCO nanotubes, the dispersion selectivity mainly goes to (6,5), (7,5), and (7,6) chiral indices, while some nanotubes with other chirality are also present in the suspension, including (8,3), (8,4), (8,6), (8,7), (9,4), (9,5), (10,2) and (10,3). In comparison with the types of SWNTs dispersed by a typical surfactant, sodium dodecylbenzenesulfonate (SDBS), in water (see Fig.…”
mentioning
confidence: 99%
“…As for many other chain-like molecules, such as DNA [36][37][38][39] and organic polymers, 21,[40][41][42] there should be other factors aside from the linkage of the polymers that affect the three-dimensional arrangement of polymer-SWCNT hybrids. For example, It is suggested that polymers with stiff and semi-exible backbones tend to wrap around the SWCNT with more distinct conformations than those with exible backbones, 43,44 which partly supports and rationalizes our conclusions.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…In these conjugated polymers, arene groups are embedded in the repeat units, which collectively engender strong binding to CNTs via π-π stacking. Experimental observations and molecular dynamic (MD) simulations have demonstrated that the polymer backbones with a certain degree of flexibility would favor wrapping around the CNTs in different fashions [43,44]. DNA or RNA molecules can interact with the CNT sidewall via π-π stacking.…”
Section: Dispersion and Release Of Cnts: A Microscopic And Supramolecmentioning
confidence: 99%